NADPH Oxidase Gene, FgNoxD, Plays a Critical Role in Development and Virulence in Fusarium graminearum - Li, Taiying; Kim, Dohyun; Lee, Jungkwan (Frontiers in Microbiology, 2022)
NADPH oxidase is an enzyme that generates reactive oxygen species from oxygen and NADPH and is highly conserved in eukaryotes. In Fusarium graminearum, a series of different Nox enzymes have been identified. NoxA is involved in sexual development and ascospore production and, like NoxB, also contributes to pathogenicity. Both NoxA and NoxB are regulated by the subunit NoxR, whereas NoxC is usually self-regulated by EF-hand motifs found on the enzyme. In this study, we characterized another NADPH oxidase in F. graminearum, FgNoxD. In the FgNoxD deletion mutant, vegetative growth and conidia production were reduced, while sexual development was totally abolished. The FgNoxD deletion mutant also showed reduced resistance to cell wall perturbing agents; cell membrane inhibitors; and osmotic, fungicide, cold, and extracellular oxidative stress, when compared to the wild type. Moreover, in comparison to the wild type, the FgNoxD deletion mutant exhibited reduced virulence against the host plant. The FgNoxD deletion mutant produced less deoxynivalenol than the wild type, and the Tri5 and Tri6 gene expression was also downregulated. In conclusion, our findings show that FgNoxD is involved in the survival against various stresses, conidiation, sexual development, and virulence, highlighting this enzyme as a new target to control the disease caused by F. graminearum.